Spray-dried egg protein in diets for early-weaned starter pigs - K Q Owen; L J Kats; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1993)
A total of 197 weanling pigs (initially 11.7 lb and 18 d of age) was used in a 28 d growth trial to determine the influence of spray-dried egg protein as a protein substitute for either soybean meal or spray-dried porcine plasma on starter pig performance. Pigs were blocked by weight with six replications per treatment and seven to eight pigs per pen. Dietary treatments were based on level of egg protein (3 or 6%) added to a phase I high nutrient dense diet and the method of substitution (egg protein replacing either soybean meal or porcine plasma). A sixth treatment served as an initial test of an egg protein blend. Treatments were as follows: 1) Control, 2 and 3) 3% or 6% egg protein substituted for soybean meal, 4 and 5) 3% or 6% egg protein substituted for spray-dried porcine plasma, and 6) 4% egg protein blend substituted for spray-dried porcine plasma. The control diet contained 7.5% porcine plasma, 1.75% spray-dried blood meal, and 20% dried whey. The egg products were substituted for the soybean meal or the porcine plasma on an equal lysine basis, maintaining the lysine level of all diets at 1.5%. Total added fat was maintained at 5% All pigs were fed a common diet from d 14 to 28 postweaning. During phase I, average daily gain (ADG) indicated that spray-dried egg protein was a suitable substitute for up to 3% porcine plasma or up to 6% soybean meal. However, pigs consuming the diet substituting 6% egg protein for porcine plasma had poorer ADG. Feed efficiency became poorer as spray-dried egg protein was substituted for 6% soybean meal or 3 to 6% porcine plasma. This indicates that the fat in spray-dried egg protein may be less available than soybean oil. Pigs fed the diet containing the 4% egg protein blend had poorer ADG and F/G than pigs fed the control diet. This indicates that 4% egg protein blend cannot effectively replace porcine plasma. These data suggest that spray-dried egg protein can replace at least 6% soybean meal and up to 3% porcine plasma in the phase I diet without reducing ADG; however, further research must be conducted to determine the digestibility of fat in the egg protein product.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Spray-dried egg protein; Starter pig